CLUSTERING PARTICIPANTS BASED ON THEIR MOTIVATIONS FOR ATTENDING 2013 MERSIN INTERNATIONAL MUSIC FESTIVAL WITHIN THE SCOPE OF EVENT TOURISM - A.Celil ÇAKICI (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2017)
Abstract Recognizing participants’ motivations is important in terms of a better planning, execution, and finalization of such events. Within this framework, a survey type of empirical research was conducted for the purpose of determining the participants’ motivations for attending the 2013 Mersin International Music Festival. The data was collected by conducting a face-to-face survey developed on the basis of the literature, which was performed by pollsters via convenience sampling method during the period of May 10-22, 2013. 421 participants took part in this research. Data was analyzed by using descriptive statistical techniques, t-test, chi-square, factor, cluster, and discriminant analysis. It was determined that the motivational factors pertaining to the participants of 2013 Mersin International Music Festival could be examined under the factors of novelty, socialization, escape, and family. This article is concluded along with the suggestion that the cluster profile should be taken into consideration and that the messages emphasizing the dimensions of escape and socialization should be used during the promotional activities of the festival. Öz Etkinlik pazarında oluşan rekabet nedeniyle, etkinlik faaliyetlerine katılanların tercihlerini neye göre yaptıkları ve en önemlisi katılımlarını sağlayan motivasyon düzeylerinin belirlenmesi, dolayısıyla etkinlik katılımcılarının motivasyonlarının bilinmesi, söz konusu etkinlikleri daha iyi planlama, yürütme, sonuçlandırma bakımından önemlidir. Bu çerçevede, Mersin Uluslararası Müzik Festivali 2013 katılımcılarının motivasyonlarını belirlemek üzere bir araştırma yapılmıştır. Bu araştırma kapsamındaki veriler, literatüre dayalı geliştirilen bir anketin, kolayda örnekleme tekniği ile 10-22 Mayıs 2013 tarihlerinde anketörler tarafından yüz yüze uygulanmasıyla toplanmış olup; araştırmaya 421 izleyici katılmıştır. Veri analizinde, tanımlayıcı istatistikler ve t-testi, ki-kare, faktör, kümeleme, ayırma analizlerinden yararlanılmıştır. Mersin Uluslararası Müzik Festivali 2013 katılımcılarının motivasyonlarının; yenilik, sosyalleşme, kaçış ve aile olmak üzere 4 ana başlıkta incelenebileceği tespit edilmiştir. Makale, festivalin tutundurma faaliyetlerinde küme profillerinin dikkate alınması gerekliliğinin yani sıra, kaçış ve sosyalleşme boyutlarına vurgu yapan mesajların kullanılması önerisiyle son bulmaktadır.